HAMBATAN PROSES PENYELESAIAN SKRIPSI MAHASISWA DENGAN STATUS MENIKAH - Esa Mukti Ageng; Agus Wibowo; Tri Anjar (Universitas Muhammadiyah Metro, 2024)
The purpose of this research is to find out the internal obstacles in the process of completing the thesis of students with married status as well as knowing the external obstacles to the process of completing student thesis with married status in the Guidance and Counseling Study Program at Muhammadiyah Metro University. This type of research is descriptive qualitative. The research subjects were students who were married in the guidance and counseling study program. The data obtained by researchers was through interview data and observations of married students in the guidance and counseling study program as research subjects. Data analysis uses the miles model, namely collecting data, reducing data, presenting data, and drawing conclusions. Data validity testing can be done by triangulating data sources.